On principal ideal multiplication modules - Azizi, A.; Jayaram, C. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Let R be a commutative ring with identity and let M be a unitary R-module. A submodule N of M is said to be a multiple of M if N = rM for some r R. If every submodule of M is a multiple of M, then M is said to be a principal ideal multiplication module. We characterize principal ideal multiplication modules and generalize some results from [Azizi A. Principal ideal multiplication modules // Algebra Colloq. – 2008. – 15. – P. 637 – 648].